PENGARUH PERSEPI KECEPATAN TERHADAP PERILAKU KONSUMTIF DENGAN PENGGUNAAN PINJAMAN ONLINE SEBAGAI VARIABEL INTERVENING - Wardani, Dewi Kusuma; Risda yani (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Online loans are a type of financial technology (fintech) that is growing rapidly in the era of information globalization. The Financial Services Authority (OJK) defines financial technology as an innovation in the financial services industry that utilizes technological developments. The purpose of this study was to determine the effect of perceived speed on consumptive behavior using online loans. This study uses a descriptive quantitative method with a research sample of 100 respondents who are undergraduate students of the tamansiswa university, shopee paylater online borrowers. Based on the test results, perceived speed affect consumption, consumption not affect actual use of online loan, and perceived speed not affect actual use of online loan with consumption as intervening variable.